The Influence of Brand Personification Mascot, Ad Engagement, and Attitude Toward Brand Mediated by Positive Emotion and Their Influence on Purchase Intention at Tiket.Com - Putranto, Achmad Ramadhani; Nirmala, Gita Chandra (Formosa Journal of Applied Sciences, 2024)
This research examines the effect of applying brand personification mascots to advertising content on tiket.com Instagram on advertising engagement and attitudes towards the brand which are mediated by positive emotions and their impact on tiket.com purchase intentions. A quantitative approach using Structural Equation Modeling (SEM) analysis, with Partial Least Square (PLS) software, was used to test 7 hypotheses. After testing, it was found that the brand personification mascot in advertising content on Tiket.com Instagram had a positive effect on advertising engagement and attitudes towards the brand through the mediation of positive emotions. Then advertising involvement also has a positive influence on attitudes towards the brand. Attitude towards the brand will have a greater influence on a person's purchase intention towards tiket.com products, while advertising involvement does not influence purchase intention.